О тождествах в алгебрах, порожденных линейно связанными идемпотентами - Рабанович, В.И.; Самойленко, Ю.С.; Стрелец, А.В. (Український математичний журнал, 2004)
Досліджено алгебри, породжені ідемпотентами, лінійна комбінація яких дорівнює одиниці, на наявність в них поліноміальних тотожностей. Доведено, що у випадку, коли кількість ідемпотентів більша або дорівнює п'яти, такі алгебри не є PI-алгебрами. У випадку чотирьох ідемпотентів для того, щоб алгебра була PI-алгеброю, необхідно і достатньо, щоб сума коефіцієнтів лінійної комбінації дорівнювала двом; у цьому випадку такі алгебри є F₄-алгебрами. We investigate the problem of the existence of polynomial identities (PI) in algebras generated by idempotents whose linear combination is equal to identity. In the case where the number of idempotents is greater than or equal to five, we prove that these algebras are not PI-algebras. In the case of four idempotents, in order that an algebra be a PI-algebra, it is necessary and sufficient that the sum of the coefficients of the linear combination be equal to two. In this case, these algebras are F₄-algebras.